EMPOWERMENT DIGITAL DIVIDE: CASE OF INTERNET ADOPTION IN UGANDA’S RURAL - URBAN AREAS - Paul, Kasse John; Munuulo, Joseph; Nagujja, Shakila (Advances in Social Sciences Research Journal, 2015)
Over the years the concept of digital divide has shifted from having to do with those who have access to technology and those who don’t because technology has become more mobile. There is wide increase in computer access in schools and personal ownership, slight decrease in computer costs, increase in internet access and wide spread access to mobile phones and services. It is no longer an issue of lack of access but being empowered to optimally use the technology or internet. Taking a rural-urban stride in Uganda‟s use of Internet, it is revealed that a regional imbalance still exists. Urban dwellers are highly empowered to use internet compared to rural dwellers as this paper will reveal. This paper therefore sets out to explore the empowerment of rural-urban dwellers to adopt Internet as an innovation taking a case of Uganda. Methodology: Quantitative and qualitative approaches were used to accomplish the study. Interview guides and questionnaires were used to collect qualitative and quantitative data respectively from internet café owners and users. Findings: Findings suggest that relative advantage, complexity, compatibility as well as trialbility being strong predictors of internet adoption. Relative advantage of the internet was found to be the strongest predictor of internet adoption in the rural urban areas. The concept of empowerment of users was found lacking and that explained the low scores on the trialbility concept.